Detection of fetal duplication 16p11.2q12.1 by next-generation sequencing of maternal plasma and invasive diagnosis. (2nd January 2019) - Chen, Min; Fu, Xiao-Ying; Luo, Yu-Qin; Qian, Ye-Qing; Pan, Ling; Wang, Li-Ya; Dong, Min-Yue
Abstract: Objective: The objective of study is to report the feasibility of non-invasive prenatal screening (NIPS) combined with invasive detection by chromosomal analysis in identifying fetal duplication, providing clinical performance of NIPS on copy number variations (CNVs) detection. Material and methods: NIPS was offered to a 35-year-old pregnant woman. Amniocentesis was performed to confirm the positive screening result. Fetal sample was detected by karyotyping, fluorescence in situ hybridization (FISH), and chromosomal microarray (CMA). Parental karyotyping was also conducted. Results: NIPS result was positive for chromosome 16, indicating an extra copy of chromosome 16. FISH and chromosomal karyotyping revealed that the fetus had a marker chromosome derived from chromosome 16. CMA further demonstrated an approximately 19-Mb duplication in chromosome 16. The final fetal karyotype was 47, XY, +mar. ish der (16)(D16Z3+).arr 16p11.2q12.1 (30 624 186–49 696 337 × 3). Ultrasound scan and MRI showed some structure malformations. Conclusions: A protocol for CNVs detection by combining a series of genetic methods was presented in this study and a novel marker duplication 16p11.2q12.1 was reported. With the ability to identify subchromosomal deletions and duplications in fetus, NIPS could reduce the possibility of invasive diagnosis. The followed confirmation test for positive sample is necessary and ensures the accuracy of the diagnosis.